Awareness and Skillfulness in Using Arabic Language Instructional Software Among Senior Secondary Schools in Kwara State - Sanusi, Taofeeq Olamilekan (Universitas Al Falah As Sunniyah Kencong Jember (UAS Press), 2025)
The study examined awareness and skillfulness in using Arabic Instructional software among senior secondary schools in Kwara state. A descriptive survey research design was used. Arabic language teachers were the respondents. There were 146 Arabic language teachers in Kwara State (Kwara State Teaching Service Commission, 2023). A sample of 108 Arabic language teachers was selected using the Kredjcie and Morgan sample size determination table. The research instrument is